ANALISIS KANDUNGAN ZAT GIZI MAKRO DAN DAYA CERNA PATI SNACK BAR TUJOGUNG (TEPUNG UBI JALAR ORANYE DAN JAGUNG) SEBAGAI ALTERNATIF MAKANAN SELINGAN PENDERITA DIABETES TIPE 2 - Ika Rahmawati (UHAMKA PRESS, 2018)
Diabetes mellitus is a group of symptoms that arise in a person experiencing an increase in blood glucose levels. Blood glucose levels can be controlled through the consumption of foods with low glycemic index and food with slowly digestible starch. The purpose of this research was to know the influence of the use of orange sweet potato flour and corn in the processing of snack bar towards macronutrients and slowly digestible starch for diabetics type 2. This research used a randomized experimental design (CRD) one variable. This research used orange sweet potato flour and corn with three ratios (25:75, 30:70, and 35:65). Hedonic test and hedonic quality test with semi-trained panelists were used to determine the selected products. Data analysis using a nonparametric test of Kruskal-Wallis resulted that the usage of the orange sweet potato flour and corn influenced the hedonic quality and hedonic of the snack bar (p<0,05). The chosen formula was a snack bar with formula 1 (25:75), which had the mean value of hedonic and hedonic quality of 3,4 and 3,7 respectively. The results of the chemical analysis of the selected snack bar were 53,4% moisture content, 2,1% ash levels, 9,3% protein, 8% fat content, and 27,3% carbohydrates. The selected snack bars continued digestible starch of 22,5%, this value was classified into the slowly digestible starch. Keywords: Corn, Orange Sweet Potato, Snack Bar, Starch Digestibility, Type 2 Diabetes